(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
Vitriolage is a medical and legal term embodying the act as well as the purpose within itself. Put simply it means "throwing acid (notably concentrated sulphuric acid / nitric acid) on some one with the malicious intent to harm that person". It has no litera meaning, and the Websters’ Third International Dictionary is silent on this terminology. However, vitriolage as a phenomenon is firmly rooted in the crucible of ages bygone. Its purpose was vitriol, i.e., hatred, then and now too. Its scope has nevertheless widened with the passage of time. Its causes’ can fan out to morbid jealousy, infidelity, vindictiveness / vengeance, gangsters’ internal warfare, etc. Out of all these the notable exception could be to disfigure the face of a woman with the intention to inscribe shame permanently on the woman. It is much akin to cutting the nose of the woman who has brought dishonor to the family. However, the present case report has beaten the oft. quoted reasons out-of-race, and hence merit its presentation solely because the manifestation -obvious and not-so-obvious -is unusual.